Activation of bimetallic AgCu foam electrocatalysts for ethanol formation from CO2 by selective Cu oxidation/reduction. (February 2020) - Dutta, Abhijit; Montiel, Iván Zelocualtecatl; Erni, Rolf; Kiran, Kiran; Rahaman, Motiar; Drnec, Jakub; Broekmann, Peter
Abstract: Bimetallic AgCu metal foams (15 at% Ag, 85 at% Cu) have been synthesized by means of an additive-assisted electrodeposition process using the dynamic hydrogen bubble template approach. Ag and Cu remain fully phase-segregated in the as deposited bimetallic foam exhibiting a high degree of dispersion of pure nm-sized Ag domains embedded in the Cu matrix. An activation of this bimetallic material towards ethanol formation is achieved by thermal annealing of the as deposited foam under mild conditions (200 °C for 12 h). Such annealing quantitatively transforms the Cu in the bimetallic system into a mixture of crystalline Cu2 O and amorphous CuO whereas the Ag remains in its metallic state due to the thermal instability of Ag2 O above temperatures of 180 °C. The selective oxidation of Cu in the bimetallic Ag15 Cu85 catalyst goes along with an enrichment of Cu oxides on the surface of the formed mixed AgCux O foam. Both operando X-ray diffraction and operando Raman spectroscopy demonstrate, however, that the oxide reduction is completed before the electrochemical CO2 reduction sets in. The thus formed oxide-derived (OD) bimetallic Ag15 Cu85 foam catalyst shows high selectivity towards alcohol formation with Faradaic efficiencies of FEEtOH  = 33.7% and FEn-PrOH  = 6.9% at −1.0 V and −0.9 V vs RHE, respectively. Extended electrolysis experiments (100 h) indicate a superior degradation resistance of the oxide-derived bimetallic catalyst which is ascribed to the effective suppression of the C1 hydrocarbon reaction pathway thus avoiding irreversible carbon contaminations appearing in particular during methane production. Graphical abstract: Image 1 Highlights: Additive-assisted AgCu co-electrodeposition yields high surface area catalysts for the CO2 RR. The AgCu foam catalyst consists of nm-sized Ag domains of (CO former) dispersed in the Cu matrix (C-C coupler). Thermal oxidation of Cu and subsequent oxide reduction during CO2 electrolysis activates the bimetallic catalyst for selective EtOH formation. Operando XRD and Raman spectroscopy are demonstrated as valuable techniques providing mechanistic insights into the EtOH formation. Extended electrolysis (100 h) indicates a superior degradation stability of the OD-bimetallic catalyst towards EtOH production.